PERUBAHAN STATUS HAK TANAH DARI HAK GUNA BANGUNAN MENJADI HAK MILIK - Mahayani, Ida Ayu Ari; Sudiarta, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 2 (2023), 2023)
Rights of building use are land rights where the land is not owned by itself but still has the right to construct and own buildings in accordance with the provisions of  Article 35 paragraph (1) of the UUPA. Building use rights are used if land is purchased in lots and the contractor who sells the land provides the land in the form of a building use rights status certificate. Many people do not realize that the term of the right to build has expired. In fact, if you want to change the status of the right to build to a property right, you can do this at the time of purchasing the land. However, the community is still indifferent to this matter, and begins to prioritize the transfer of usufructuary rights to become property rights when there is a transaction on the land, for example at the time of land sale. The problem that will be studied in this paper is about how the existence and legal certainty in guaranteeing land with the status of usufructuary rights that have expired and the obstacles in the process of changing land from usufructuary rights to land ownership rights. Normative legal research is the method with a statutory approach. The status of Building Use Rights that are still valid or those that have expired are regulated in PP Number 18 of 2021. As well as obstacles that occur in the process of changing rights from HGB to property rights such as timeframe and costs, citizen need to be aware for the legal of building use rights. Indonesian citizens need to pay more attention to the land rights they own, so that later mistakes will not occur, especially in the administration related to land rights.